Qibla Direction Training for the Million People of South Galesong District, Takalar Regency - Sartika Sartika; Hisbullah Salam; Riski Amalia; M. Amil Arfah; Nanda Nanda; Alamsyah Alamsyah (MALLOMO: Journal of Community Service, 2026)
This community service activity aimed to improve public knowledge and practical skills in determining accurate Qibla direction for places of worship and cemeteries in South Galesong District, Takalar Regency. The activity was carried out through coordination with local partners, socialization on the urgency of Qibla accuracy, training in the use of compasses, Istiwa'aini instruments, smartphone-based Qibla applications, field practice, calibration at selected mosques and cemeteries, and evaluation through observation, discussion, and comparison of measurement results. Data were analyzed descriptively by examining participant responses, field participation, and differences between existing Qibla directions and measured results. The activity showed that community knowledge of Qibla measurement methods and supporting technology was still limited, while participants responded positively to direct training and field assistance. Measurements on mosque and cemetery samples found deviations of fifteen to twenty-six degrees from the accurate Qibla direction. The program concluded that integrated socialization, instrument practice, and field calibration can strengthen community capacity to check and correct Qibla direction independently and sustainabl